Penerapan Direct Method dalam Meningkatkan Prestasi Belajar Peserta Didik pada Mata Pelajaran Bahasa Arab Kelas 1C MTs di Pondok Pesantren Daarul Rahman Jakarta - Ahmad Syarifudin (Tarbiatuna: Journal of Islamic Education Studies, 2024)
This research is motivated by the problem of low grades in Arabic language learning subjects in class 1C MTs Daarul Rahman Islamic Boarding School, South Jakarta. The research method used is Classroom Action Research (PTK), data collection techniques with observation, oral and written tests, documentation. In this study, the subjects were students of class 1C MTs Daarul Rahman Islamic Boarding School, South Jakarta in the 2022/2023 school year consisting of 40 students. The object in this study is the improvement of students' learning achievement in Arabic language subjects using the direct method of class 1C MTs Daarul Rahman Islamic Boarding School, South Jakarta. The increase in students' learning achievement in Arabic language subjects has increased, it can be seen from each cycle that changes have occurred. In the pre-cycle the results were 62%, increased in cycle 1 with a result of 66%, and in cycle 2 increased with a result of 73%. From the learning activities that have been carried out, the learning achievement of students' Arabic language has increased and has reached the predetermined success criteria, it shows that the direct method is successful in improving students' Arabic language in class 1C MTs Daarul Rahman Islamic Boarding School, South Jakarta.